2016
DOI: 10.1039/c6mb00217j
|View full text |Cite
|
Sign up to set email alerts
|

The bovine milk microbiota: insights and perspectives from -omics studies

Abstract: Recent significant progress in culture-independent techniques, together with the parallel development of -omics technologies and data analysis capabilities, have led to a new perception of the milk microbiota as a complex microbial community with great diversity and multifaceted biological roles, living in an environment that was until recently believed to be sterile. In this review, we summarize and discuss the latest findings on the milk microbiota in dairy cows, with a focus on the role it plays in bovine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
202
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(212 citation statements)
references
References 174 publications
(226 reference statements)
6
202
0
4
Order By: Relevance
“…It is possible that the microbiome of the mammary gland present itself as stable and resilient, comparable to what was observed in the salivary microbiome. This hypothesis is corroborated by the highly diverse microbiome of healthy milk described in many studies [61, 66, 67]. One could also speculate that the healthy milk microbiome does not contain strains of bacteria that are resistant to ceftiofur and capable of taking advantage due to the lack of competition imposed by antimicrobial exposure.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It is possible that the microbiome of the mammary gland present itself as stable and resilient, comparable to what was observed in the salivary microbiome. This hypothesis is corroborated by the highly diverse microbiome of healthy milk described in many studies [61, 66, 67]. One could also speculate that the healthy milk microbiome does not contain strains of bacteria that are resistant to ceftiofur and capable of taking advantage due to the lack of competition imposed by antimicrobial exposure.…”
Section: Discussionmentioning
confidence: 57%
“…It is possible that the observed lack of change in the relative abundance could be accompanied by differences in the metabolic profile of bacteria exposed to antimicrobials. Using technologies such as shotgun metagenomics, metabolomics, and proteomics [61], we could detect differences not evident by 16S rRNA sequencing, and conclusions about the effects of cephalosporins in the diseased mammary gland may change.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the milk microbiome has been a daunting task41, particularly in clinical mastitis with negative culture results10. Various reasons could explain why a negative result might be obtained from a mastitic milk culture: the microorganisms associated with the infection might be shed intermittently; or the number of viable bacterial cells is small; finally, the cow’s immune system might have eliminated the pathogen, and the observation of abnormal milk could be a consequence of the inflammatory process that occurred during destruction of the pathogen42.…”
Section: Discussionmentioning
confidence: 99%
“…We may also have falsely classified some infected glands as uninfected because the pathogen levels were below the limit of detection by conventional culture techniques. Recent studies utilizing multiplex real‐time PCR and PCR amplification and sequencing of 16 rRNA gene fragments (16S metagenomics) have suggested that milk obtained from healthy mammary glands may be colonized by a variety of microbes . An unresolved question is whether these observations reflect contamination of the milk sample during the collection process or localized colonization in the teat orifice, streak canal, and teat cisternal milk, instead of generalized microbial colonization of alveolar and gland cisternal milk .…”
Section: Discussionmentioning
confidence: 99%